Analisis Pragmatik Tindak Tutur Direktif Dalam Interaksi Guru Dan Siswa Di Kelas - Icha Theresya Barasa (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the forms, types, and functions of directive speech acts in teacher–student classroom interaction from a pragmatic perspective. The research employed a qualitative approach using a descriptive method. The data consisted of spoken utterances collected during classroom teaching and learning activities through observation, audio-video recording, and note-taking techniques. Data analysis was conducted by identifying and classifying directive speech acts based on Searle’s speech act theory while considering the contextual aspects of the utterances. The findings reveal that directive speech acts are the most dominant type used by teachers, with commands and instructions occurring most frequently. In terms of linguistic forms, directive speech acts are realized through imperative, declarative, and interrogative sentences. The use of directive speech acts is influenced by classroom conditions, instructional objectives, and students’ responses. This study concludes that the varied use of directive speech acts combined with politeness strategies plays a significant role in creating effective and conducive classroom interaction.